Is the decrease of the total electron energy density a covalence indicator in hydrogen and halogen bonds? - Angelina, Emilio Luis (2013)
In this work, halogen bonding (XB) and hydrogen bonding (HB) complexes were studied with the aim of analyzing the variation of the total electronic energy density H(rb) with the interaction strengthening. The calculations were performed at the MP2/6-311++G(2d,2p) level of approximation. To explain the nature of such interactions, the atoms in molecules theory (AIM) in conjunction with reduced variational space self-consistent field (RVS) energy decomposition analysis were carried out. Based on the local virial theorem, an equation to decompose the total electronic energy density H(rb) in two energy densities, (-G(rb)) and 1/4Lap rho(rb), was derived. These energy densities were linked with the RVS interaction energy components. Through the connection between both decomposition schemes, it was possible to conclude that the decrease in H(rb) with the interaction strengthening observed in the HB as well as the XB complexes, is mainly due to the increase in the attractive electrostatic part of the interaction energy and in lesser extent to the increase in its covalent character, as is commonly considered.